Vertebra collapse due to primary amyloidosis causing neurological compromise. (31st May 2013) - Yoshihara, Hiroyuki; Nojiri, Kenya; Yabe, Mariko; Takahata, Takeshi
Abstract : In primary amyloidosis (AL), a fibrillar protein (amyloid light chain) is deposited in many organs; however, it is rare to have involvement of the vertebral bodies. Multiple myeloma is a well-known systemic amyloid disease that frequently has vertebral involvement. However, the pathology of vertebral involvement of these two clinical entities differs significantly. We report a patient with L4 vertebral collapse because of primary AL, causing neurological compromise that improved with surgical treatment. Deposition of amyloid and following demineralisation caused the vertebral collapse. Primary AL needs to be taken into consideration as a cause of pathological vertebral fracture.